Revealing Downturns - Martin C. Schmalz; Sergey Zhuk (Center for Economic Studies and ifo Institute (CESifo), 2018)
When Bayesian risk-averse investors are uncertain about their assets' cash flows' exposure to systematic risk, stock prices react more to news in downturns than in upturns, implying higher volatility in downturns and negatively skewed returns. The reason is that, in good times, less desirable assets with low average cash flows and high loading on market risk perform similar to more desirable assets with high average cash flows and low market risk, rendering them difficult to distinguish. However, their relative fundamental performance diverges in downturns, enabling better inference. Consistent with these predictions, stocks' reaction to earnings news is up to 70% stronger in downturns than in upturns..
Keywords: 330; financial economics; finance